PENGARUH PEMANFAATAN ARTIFICIAL INTELLIGENCE TERHADAP MOTIVASI BELAJAR MAHASISWA FAKULTAS TEOLOGI DI UNIVERSITAS KRISTEN TEKNOLOGI SOLO - Babu, Orni; Wening, Sri (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2025)
Learning motivation is a crucial element for student success, and this holds true for students at the Faculty of Theology, Christian University of Technology Surakarta. It not only helps students start the learning process but also sustains their enthusiasm for understanding and mastering course material, ultimately leading to the achievement of learning goals. This research aims to determine the influence of utilizing Artificial Intelligence (AI) on the learning motivation of students at the Faculty of Theology, Christian University of Technology Surakarta. After processing the data using SPSS 25, the results showed a significant influence of AI utilization on the learning motivation of theology students. The correlation table reveals the strength of the relationship between the independent and dependent variables. The correlation coefficient is 0.299, which, based on the interpretation guidelines for correlation coefficients, falls within the range of 0.299 - 0.40. This indicates that the utilization of artificial intelligence has an influence on the learning motivation of the Faculty of Theology students. Therefore, it is expected that the use of artificial intelligence can help theology students enhance their learning motivation. ABSTRAK Motivasi belajar menjadi salah satu elemen penting terhadap keberhasilan mahasiswa dalam keberhasilan belajar, begitu juga bagi mahasiswa di Fakultas Teologi Universitas Kristen Teknologi Solo. Motivasi belajar tidak hanya membantu mahasiswa untuk memulai proses belajar, tetapi juga mempertahankan semangat belajar dalam usaha memahami dan mendalami materi perkuliahan sehingga tujuan belajar tercapai. Penelitian ini bertujuan untuk mengetahui bagaimana pengaruh pemanfaatan Artificial Intelligence (AI) terhadap motivasi belajar mahasiswa Fakultas Teologi di Universitas Kristen Teknologi Solo, setelah melakukan pengolahan data menggunakan SPSS 25 dan diketahui bahwa terdapat pengaruh signifikan dari pemanfaatan artificial intelligence terhadap motivasi belajar mahasiswa Fakultas Teologi. Dengan melihat tabel korelasi menunjukkan besar hubungan variabel bebas terhadap variabel terikat. Terlihat dari kolom kefisien korelasinya sebesar 0,299 Berdasarkan pedoman interpretasi koefisien korelasi antara 0,40 – 0,299. Dengan demikian pemanfaatan artificial intelligence berpengaruh dalam motivasi belajar mahasiswa Fakultas Teologi. Oleh karena itu, diharapkan pemanfaatan artificial intelligence dapat membantu mahasiswa Fakultas Teologi dalam meningkatkan motivasi belajar.